PENDEKATAN NARATIF DALAM KONSELING RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) UNTUK MENGELOLA EMOSI - Purbaning Tyas, Prias Hayu (JURNAL FOKUS KONSELING, 2015)
AbstractÂ The research aims to obtain an overview of the effectiveness of the narrative approach in counseling Rational Emotive Behavior Therapy (REBT) to manage emotions. The approach used in this study is a quantitative approach using a quasi-experimental methods. The study design used is one group pretest-posttest design using purposive sampling technique. The samples were 6 students who score low emotion management. The instrument used in the form of guidelines for the interview to express emotion management profile of students in class X. The results showed that: (1) there are 6 students of 14 students interviewed, have a tendency to be difficult to manage emotions appropriately; (2) The narrative approach in counseling REBT apparently quite effective for improving emotional intelligence on aspects of self-awareness, self-regulation, self-motivation, empathy, and social skills. This recommendation is addressed to the teacher guidance and counseling, further research, and study of Guidance and Counseling Program. Â Keywords: counseling REBT, narrative approach, manage emotions.